Common mycorrhizal networks activate salicylic acid defense responses of trifoliate orange (Poncirus trifoliata) - Zhang, Yi-Can; Zou, Ying-Ning; Liu, Li-Ping; Wu, Qiang-Sheng (Journal of integrative plant biology, 2019)
Citrus canker, caused by Xanthomonas axonopodis pv. citri ('Xac'), is an important quarantine disease in citrus crops. Arbuscular mycorrhizal fungi (AMF) form symbiotic interactions with host plants and further affect their disease resistance, possibly by modulating the activity of salicylic acid (SA), a key phytohormone in disease resistance. Common mycorrhizal networks (CMNs) can interconnect plants, but it is not yet clear whether CMNs promote resistance to citrus canker and, if so, whether SA signaling is involved in this process. To test this possibility, we used a two-chambered rootbox to establish CMNs between trifoliate orange (Poncirus trifoliata) seedlings in chambers inoculated (treated) or not (neighboring) with the AMF, Paraglomus occultum. A subset of the AMF-inoculated seedlings were also inoculated with Xac (+AMF+Xac). At 2 d post-inoculation (dpi), compared with the +AMF-Xac treatment, neighboring seedlings in +AMF+Xac treatment had lower expression levels of the SA biosynthetic genes, PtPAL, PtEPS1, and PtPBS3, but higher SA levels, which attributed to the upregulation of PtPAL and PtPBS3 in treated seedlings and the transfer of SA, via CMNs, to the neighboring seedlings. At 4 dpi, the pathogenesis-related (PR) protein genes, PtPR1, PtPR4, and PtPR5, and the transcriptional regulatory factor gene, PtNPR1, were activated in neighboring seedlings of +AMF+Xac treatment. At 9 dpi, root phenylalanine ammonia-lyase activity and total soluble phenol and lignin concentrations increased in neighboring seedlings of +AMF+Xac treatment, likely due to the linkage and signal transfer, via CMNs. These findings support the hypothesis that CMNs transfer the SA signal from infected to neighboring healthy seedlings, to activate defense responses and affording protection to neighboring plants against citrus canker infection.
Keywords: Salicylic Acid; Xanthomonas axonopodis; kyselina salicylová; Poncirus